E-Counseling Pelayanan Kesehatan Anak Dimasa Covid 19 Berbasis Mobile (Studi Kasus : Puskesmas Kenten) - Evi Yulianti; Dona Marcelina (UNIVERSITAS INDO GLOBAL MANDIRI)
With the COVID-19 outbreak and many conveniences in building mobile-based service applications. The Information System application can monitor children's health during the actual covid 19 pandemic online which can provide preventive and treatment measures during this pandemic period that we can do independently at home. By synergizing the e-counselling program for mobile-based child health services at the Kenten Palembang Health Center. Through a mobile-based e-counselling information system, it becomes a forum for information for mothers with toddlers who need health counseling services for children's diseases in the vicinity. The forward chaining method used in collecting data and information from the management and doctors of the Kenten Health Center with knowledge of the disease process by means of interviews, it was found that the facts most experienced by the surrounding community were the first types of facts, complaints, symptoms and suggestions for handling the two research rules by The third disease is how to implement E-Counseling for mobile-based Child Health Services. With the characteristics of the disease, symptoms, treatment, prevention. While the potential for online-based software development uses the waterfall method with technical use case diagrams, activity diagrams and class diagrams. MySql server application, Web server is used to support database creation. The results of this study can provide input and benefits, especially in child health service activities around the Kenten Palembang Health Center.Keywords: E-Counseling, forward chaining, waterfall, mobile-based